Dificuldade de aprendizagem da leitura e escrita: desafios e possibilidades na Comunidade São Pedro - Santa Maria do Pará - SANTOS, Leida Maria da Silva (2019)
The paper has the theme “Difficulty of Learning Reading and Writing: challenges and possibilities in the community of São Pedro-Santa Maria do Pará”. It is justified, therefore, the theme is a reflection of my uneasiness before an educational reality of the students of MEIF School. Antônio Henrique de Oliveira. It is worth noting that the problem arose from the need to understand better, that in the construction of the intellectual development of each student, there are factors that interfere in the learning process, causing serious problems or learning difficulties to their school life. The main objective is to analyze the main factors that make reading and writing difficult for second year students in the Multisserie group of the Elementary School of the MEIF School Antônio Henrique de Oliveira, in the Travessa São Pedro community, Santa Maria do Pará. Specific objectives: Identify the main difficulties of reading and writing are presented by the students of the second year of Elementary School. Note that factors that contribute to the maintenance of the main difficulties of reading and writing are presented by the students of the second year of Elementary School. Perceiving the teacher's pedagogical practices can contribute to the learning of reading and writing. They are authors: Antunes (2003), Fernandes (2006), Ferreiro (2004), Kleiman (2005), Lajolo (1999), Oliveira (1996), Silveira (1997), Soares (2005/2004/2009/2010), Teberosky (2008), Vigotski (2007), and others. It is concluded that it was possible to identify that the main difficulties of reading and writing are presented by the students of the second year of EF in the school in question are to maintain concentration and attention in the context of the multisserie group where the age brackets are large, as well as the contents to be worked, which causes discouragement and demotivation.